2012
DOI: 10.1002/cbf.2866
|View full text |Cite
|
Sign up to set email alerts
|

The protection by heme oxygenase‐1 induction against thioacetamide‐induced liver toxicity is associated with changes in arginine and asymmetric dimethylarginine

Abstract: This study was designed to investigate the role of HO-1 induction in prevention of thioacetamide (TAA)-induced oxidative stress, inflammation and liver damage. The changes in hepatic dimethylarginine dimethylaminohydrolase (DDAH) activity as well as plasma arginine and asymmetric dimethylarginine (ADMA) levels were also measured to evaluate nitric oxide (NO) bioavailability. Rats were divided into four groups as control, hemin, TAA and hemin + TAA groups. Hemin (50 mg kg(-1) , i.p.) was injected to rats 18 h b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Recently, Mookerjee (Mookerjee et al 2015) reported a decreased expression of DDAH-1 isoform in the liver of cirrhotic patients. Moreover, in TAA-induced ALF in rodents, an increase in plasma ADMA level was shown to correlate with the reduced activity of DDAH in the liver (Bekpinar et al 2015; Develi-Is et al 2013) and brain tissue (Milewski et al 2015). An increased ADMA content in plasma and brain tissue have also been reported in rat models of chronic cirrhosis (Balasubramaniyan et al 2012; Laleman et al 2005; Mookerjee et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mookerjee (Mookerjee et al 2015) reported a decreased expression of DDAH-1 isoform in the liver of cirrhotic patients. Moreover, in TAA-induced ALF in rodents, an increase in plasma ADMA level was shown to correlate with the reduced activity of DDAH in the liver (Bekpinar et al 2015; Develi-Is et al 2013) and brain tissue (Milewski et al 2015). An increased ADMA content in plasma and brain tissue have also been reported in rat models of chronic cirrhosis (Balasubramaniyan et al 2012; Laleman et al 2005; Mookerjee et al 2015).…”
Section: Introductionmentioning
confidence: 99%